Comparative evaluation of conventional and real-time PCR assays for detecting Bacteroides fragilis in clinical samples. - Papaparaskevas, Joseph; Mela, Victoria; Houhoula, Dimitra P; Pantazatou, Angeliki; Petrikkos, Georgios L; Tsakris, Athanassios (J Clin Microbiol, 2013)
A conventional PCR and a real-time PCR for detecting Bacteroides fragilis were evaluated against clinical specimens. Analytical sensitivities were 100 and 40 fg of DNA, respectively. Detection limits were 100 and 10 CFU/ml, respectively. A total of six culture-negative specimens were positive by PCR. Altering the gold standard from "positive culture" to "positive culture or both PCR assays positive" resulted in sensitivities of 91.7% and 100%, respectively, and in specificities of 100% and 98.6%, respectively.
Keywords: Bacteroides fragilis; Bacteroides Infections; DNA, Bacterial; Feces; Humans; Limit of Detection; Real-Time Polymerase Chain Reaction; RNA, Ribosomal, 16S; Sensitivity and Specificity